2012
DOI: 10.4236/abc.2012.21007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of eco-friendly coagulant from <i>Trigonella foenum-graecum</i> seed

Abstract: The ability of seed extracts of Trigonella foenum-graecum (T. foenum-graecum) and Cuminum cyminum (C. cyminum) to act as natural coagulants was tested using natural turbid water. Seed extracts were prepared using distilled water and NaCl (0.5 M and 1.0 M) solution. Only 1.0 M NaCl extract of T. foenum-graecum had coagulation capability and did not depend on pH values. Further it showed that natural coagulant obtained from T. foenum-graecum is temperature (up to 100˚C) and pH stable (pH 4.0 -10.0). Extract of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…Maximum coagulation property is of Aluminum Sulphatei.e 90-97% as compare to natural coagulants T. foenum-graecum, Strychnospotatorum, Moringaoleifera and Aluminum Sulphate. After Aluminum Sulphate, T. foenumgraecum has good coagulation property which used for treatment of water and showed decrease in alkalinity, turbidity, KMnO 4 demand and total coliform [2].…”
Section: Summery Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Maximum coagulation property is of Aluminum Sulphatei.e 90-97% as compare to natural coagulants T. foenum-graecum, Strychnospotatorum, Moringaoleifera and Aluminum Sulphate. After Aluminum Sulphate, T. foenumgraecum has good coagulation property which used for treatment of water and showed decrease in alkalinity, turbidity, KMnO 4 demand and total coliform [2].…”
Section: Summery Of Literaturementioning
confidence: 99%
“…The pods are non-toxic natural organic polymer and effective sorbent for the removal of organics and for coagulation of water treatment as ds contains naturalpolyelectrolyte. The best and efficient removal was observed at pH7.0-9.It is concluded that the MO seeds have the potential to be used in the dairy industry waste water treatment in an efficient way and with low cost.Chitteti Ramamurthy et al, (2012)[2]describes that the ability of seed extracts of Trigonellafoenumgraecum (T. foenum-graecum) and Cuminumcyminum (C. cyminum) to act as natural coagulants. These extracts tested using natural turbid water and prepared using distilled water and NaCl (0.5 M and 1.0 M) solution.…”
mentioning
confidence: 99%
“…This could provide an overview on the structure and surface characteristics which may lead to better understanding on the bonding of colloidal particles (Idris et al, 2013). Ramamurthy et al (2012) Extensive studies to conclude the respective coagulation mechanism involved in each of the plant-based coagulants are also limited. The aggregation of colloidal particles leading to water clarification could be a result of one or more coagulation mechanisms.…”
Section: Limitations and Further Improvements On The Current Natural mentioning
confidence: 99%
“…Solo el 2,5% constituye la disponibilidad de agua dulce de la tierra, originando preocupación con respecto al uso y calidad del preciado líquido [2]. Su escases genera una vida más difícil, a pesar de la conciencia al respecto, son muy pocos los esfuerzos realizados para prevenir la contaminación de los recursos hídricos [3], [4]. Su deterioro, pérdida y demanda han aumentado en los últimos años debido a diversos factores, tales como: la sobreexplotación de tierras, el crecimiento poblacional, la expansión urbana, aumento de la actividad económica e industrialización [3], [5].…”
Section: Introductionunclassified
“…Su escases genera una vida más difícil, a pesar de la conciencia al respecto, son muy pocos los esfuerzos realizados para prevenir la contaminación de los recursos hídricos [3], [4]. Su deterioro, pérdida y demanda han aumentado en los últimos años debido a diversos factores, tales como: la sobreexplotación de tierras, el crecimiento poblacional, la expansión urbana, aumento de la actividad económica e industrialización [3], [5]. Diversas organizaciones internacionales realizan conferencias y campañas de concientización en donde el mensaje principal es el reconocimiento y aceptación del agua como un recurso finito que no puede caer en la dilapidación y abuso [1].…”
Section: Introductionunclassified